The Role of Teachers in Schools in Fostering Social Relationships of Students - Sri Syahraini Caniago; Munawir Pasaribu; Selamat Pohan (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
Student social interaction in the school environment is an essential factor in shaping the character and morals of the younger generation. Teachers have a strategic role as educators, mentors, and role models in guiding healthy social interactions by moral and religious values. This study aims to describe and analyze the role of teachers in fostering student social interactions at SMAN 1 Lae Parira, while assessing its alignment with Islamic educational principles. The study employs a qualitative approach, using data collection techniques through interviews with five teachers and 76 students from grades 10 to 12. The study results show that teachers actively set positive examples, remind students of the importance of good manners, guide students away from promiscuity, and monitor student interactions inside and outside the classroom. Teachers also pay special attention to students who exhibit deviant behavior and involve students in activities that support healthy social interaction. Despite challenges, such as students' varying comfort levels in discussing personal issues, teachers are generally assessed as actively and positively fulfilling their roles. This study concludes that teachers at SMAN 1 Lae Parira foster student social interactions that align with Islamic educational values ??and contribute significantly to creating a socially and spiritually conducive school environment